2015
DOI: 10.1101/gad.260562.115
|View full text |Cite
|
Sign up to set email alerts
|

Sex comb on midleg (Scm) is a functional link between PcG-repressive complexes inDrosophila

Abstract: The Polycomb group (PcG) proteins are key regulators of development in Drosophila and are strongly implicated in human health and disease. How PcG complexes form repressive chromatin domains remains unclear. Using crosslinked affinity purifications of BioTAP-Polycomb (Pc) or BioTAP-Enhancer of zeste [E(z)], we captured all PcG-repressive complex 1 (PRC1) or PRC2 core components and Sex comb on midleg (Scm) as the only protein strongly enriched with both complexes. Although previously not linked to PRC2, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 106 publications
3
94
0
2
Order By: Relevance
“…The same binding site is recognized by the GAF and Psq protein pair, despite that they have different types of DNA-binding domains [124] ( Table 1). The binding site of the Zeste protein is also recognized by the Fs(1)h (female sterile (1) homeotic) protein, which has been characterized as a TrxG factor [154] and, at the same time, purifies with the PRC1 complex when tagged with the Pc protein [155,156]. The recruitment of Fs(1)h to PREs and its implication in PcG function are yet to be verified.…”
Section: Role Of Protein Binding Sites In Repressionmentioning
confidence: 99%
“…The same binding site is recognized by the GAF and Psq protein pair, despite that they have different types of DNA-binding domains [124] ( Table 1). The binding site of the Zeste protein is also recognized by the Fs(1)h (female sterile (1) homeotic) protein, which has been characterized as a TrxG factor [154] and, at the same time, purifies with the PRC1 complex when tagged with the Pc protein [155,156]. The recruitment of Fs(1)h to PREs and its implication in PcG function are yet to be verified.…”
Section: Role Of Protein Binding Sites In Repressionmentioning
confidence: 99%
“…Using parallel TAP-tagged purification approaches, it was shown that SCM is the only protein, which is enriched in both PRC1 and PRC2 type complexes. It seems that the SAM domain containing SCM protein can offer the functional link between Polycomb repressive complexes [141].…”
Section: Discovery Of Polycomb Repressive Complexesmentioning
confidence: 99%
“…BioTAP-XL has successfully identified key interactors of the male-specific lethal (MSL) dosage compensation and heterochromatin protein (HP1a) complexes in Drosophila (5) and revealed novel components of the Polycomb Repressive Complex 2 in human tissue culture cells (6) and fruit flies (7). Despite the aforementioned advantages, BioTAP-XL suffers from several limitations.…”
mentioning
confidence: 99%